School Social Work in a Global Context - Leticia Villarreal Sosa; Michael S. Kelly (International Journal of School Social Work, 2017)
We are pleased to announce our second issues of the International Journal of School Social Work (IJSSW). With its publication, IJSSW continues our focus on providing open access to evidence based and peer reviewed literature to school social workers around the world. As social workers, our practice is inherently global regardless of where we practice and by creating ways to share information across borders. When we practice from a global social work perspective, we appreciate diversity and understand global issues that face the students and families we serve. In particular, this understanding comes with special attention to differences in privilege, and access to resources as a result of that privilege. As we do work across national borders, the importance of both evidence-based practice and the development of local knowledge have been magnified by the increasing demand to demonstrate student outcomes as well as the expanding international scope of school social work practice. This journal will allow school social workers from around the world greater access to current research, and for the exchange of resources, knowledge, and perspectives.
Keywords: school social work; global social work; international school social work